Case Report: SMARCB1-deficient phenotype may be a new specialized type of pleomorphic xanthoastrocytoma associated with poor prognosis - Zhang, Hui; Xiang, Xueping; Ma, Xiaojing; Zhang, Buyi; Xu, Susu; He, Xiaojuan; Xu, Jinghong (Frontiers in Oncology, 2025)
Pleomorphic xanthoastrocytoma (PXA) is a rare, localized glioma characterized by frequent BRAF V600E mutations and CDKN2A/B deletions. Compared to IDH-wildtype glioblastoma, PXA has a better prognosis. Recently, rare cases of PXA with rhabdoid histological characteristics have been reported, which are titled atypical teratoid/rhabdoid tumor arising in a PXA. However, the genetic characteristics of these cases have rarely been investigated. Herein, we present a 49-year-old woman with a mass in the left frontotemporal region. Microscopically, this mass is composed of the glial and rhabdoid elements, both of which have molecular features of PXA, and the rhabdoid elements assessed using immunohistochemistry for SMARCB1 (INI1) expression demonstrated expression loss. The DNA methylation profile showed a significant calibrated score of 0.81 for methylation class PXA. The tumor was eventually diagnosed as a PXA with SMARCB1 deficiency.